Rancang Bangun Payroll System PT. Konsuil Perdana Indonesia Area Bogor - Artika Surniandari; Nurma Safitri (Jurnal Teknik Komputer AMIK BSI, 2022)
Utilization of Information Technology to support the quality of information has a positive impact, because to obtain the required information, it is necessary to pay attention to the quality of the data and the processing process. The internet is also a very potential means to carry out office activities. Based on the above ideas, scientific writers will discuss the creation of a web-based application as a support for the payroll information system. The purpose of making this website is to make it easier for admins if they want to manage payroll data, besides that it can be more effective and time efficient, especially for business people who usually don't have much time. The software development method used is the waterfall method with PHP, HTML, MySQL, Dreamweaver as the software used. PHP itself was chosen because of its scripting language and it is widely used to create web because of the dynamics and complexity in various databases. With the use of the waterfall method, it is hoped that the web can function properly and get the desired results